Development of Modification of Big Ball Game with Play Approach in Order to Develop Basic Movement Skills in Elementary School Students - Indah Verawati; Rahma Dewi; Doris Apriani Ritonga (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to modify the basic motion-based big ball game with a play approach in order to develop basic movement skills and be developed as a guide for sports teachers and learning with game concepts. The resulting product is a CD and a good ball game manual with a playing approach. The research was developed by adapting the Gall, Gall, & Borg educational research and development model. The development procedure used includes several stages: 1) analyzing the content of the developed product, 2) developing the initial game product, 3) expert validation, 4) field testing, 5) product revision of the data analysis techniques used in this study in two ways, namely quantitative and qualitative.